The impact of a multi-micronutrient nutritional formula combined with cognitive behavioral therapy in managing symptoms of children with attention deficit hyperactivity disorder - Wang, Yun; Cao, Meng (Frontiers in Pediatrics, 2025)
BackgroundAttention-Deficit/Hyperactivity Disorder (ADHD) characterized by symptoms of inattention, hyperactivity, and impulsivity, with substantial impacts on a child's academic performance, social interactions, and overall quality of life. This study investigates the impact of combining a multi-micronutrient nutritional formula (MNF) with cognitive behavioral therapy (CBT) in managing ADHD symptoms in children.MethodsIn a retrospective analysis of 220 children aged 6–14 years diagnosed with ADHD, patients were divided into two groups: the MNF group (n = 112) receiving only the nutritional formula, and the MNF-CBT group (n = 108) receiving both the nutritional formula and CBT. The interventions were conducted over three months. Outcomes were measured using the Conners Parent Symptom Questionnaire (PSQ), SNAP-IV Teacher Form, and Dundee Difficult Times of the Day Scale (D-DTODS).ResultsBoth groups were comparable at baseline in terms of demographics and ADHD symptom severity. Post-treatment analyses revealed greater reductions in attention deficit scores, hyperactivity/impulsivity scores, and oppositional symptoms scores in the MNF-CBT group compared to the MNF group. Conduct scores were lower in the MNF-CBT group than in the MNF group, and learning scores also showed a similar pattern of reduction. Functional impairments across various daily activities, as measured by the D-DTODS, were also reduced in the MNF-CBT group. No adverse events or safety concerns were observed during the intervention period.ConclusionThe combination of multi-micronutrient supplementation with CBT shows potential in alleviating both neurochemical deficiencies and behavioral dysregulation in children with ADHD. These findings suggest that this integrated approach may be beneficial for managing ADHD symptoms.